Surgical Management of Multiple Cerebral Hydatid Cysts without Systemic Involvement: A Case Report - Radu, Roxana; Azevedo, Miguel; Neacșu, Angela; Zaharia, Marius Cristian; Gorgan, Radu Mircea (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Hydatidosis is a rare and serious parasitic disease caused by Echinococcus granulosus larvae, with central nervous system (CNS) involvement being a potentially fatal complication. We present a case of neurohydatidosis in a 55-year-old male farmer exhibiting symptoms of the left parietal syndrome. Imaging studies revealed six well-defined, non-enhancing cystic lesions in the left parietal lobe, and serological evaluation confirmed the presence of Echinococcus-specific IgG antibodies. A chest-abdomen-pelvis CT scan showed no additional hydatid cysts in other organs.The patient underwent microsurgical resection of all six cerebral parietal cysts without rupture, using Dowling's maneuver of hydrodissection with isotonic saline solution. Intraoperatively, the membrane of a previously ruptured seventh cyst was found and excised, and the remaining cavity was irrigated with hypertonic saline solution to prevent recurrence. The patient recovered well without any new neurological deficits or postoperative complications, and a histopathological examination confirmed the diagnosis. He was discharged with previous symptoms in remission and continued antihelminthic treatment with albendazole for 28 days.Cerebral cystic echinococcosis should be included in the differential diagnosis for patients with multiple cystic lesions in the brain. This case report highlights the unusual presentation of multiple cerebral hydatid cysts without the involvement of other parenchymal organs. Surgical resection using hydrodissection combined with antihelminthic therapy is an effective treatment approach for neurohydatidosis.
Keywords: echinococcus granulosus; cerebral hydatid cysts; dowling's technique; antihelminthic therapy